2008
DOI: 10.1128/aem.02532-07
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation-Independent Characterization of Methylobacterium Populations in the Plant Phyllosphere by Automated Ribosomal Intergenic Spacer Analysis

Abstract: Bacteria of the genus Methylobacterium are widespread in the environment, but their ecological role in ecosystems, such as the plant phyllosphere, is not very well understood. To gain better insight into the distribution of different Methylobacterium species in diverse ecosystems, a rapid and specific cultivationindependent method for detection of these organisms and analysis of their community structure is needed. Therefore, 16S rRNA gene-targeted primers specific for this genus were designed and evaluated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 60 publications
(63 reference statements)
3
54
1
5
Order By: Relevance
“…It has been shown that different plant species grown at the same site harbored communities of different complexity, a finding that is supported by the results of cultivation-dependent studies Raja et al, 2008). Individuals of the same plant species harbored very similar Methylobacterium communities, which differed from those of some other plant species grown at the same site, suggesting a certain degree of plant species specificity (Knief et al, 2008).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…It has been shown that different plant species grown at the same site harbored communities of different complexity, a finding that is supported by the results of cultivation-dependent studies Raja et al, 2008). Individuals of the same plant species harbored very similar Methylobacterium communities, which differed from those of some other plant species grown at the same site, suggesting a certain degree of plant species specificity (Knief et al, 2008).…”
Section: Introductionmentioning
confidence: 77%
“…The presence of Methylobacterium strains in the phyllosphere has been shown in numerous studies, but information on the composition of this community on plants and the factors that affect composition is limited and derives mostly from cultivationdependent methods, based on the analysis of a restricted number of isolates. Recently, Methylobacterium communities were for the first time analyzed by a cultivation-independent method (Knief et al, 2008). It has been shown that different plant species grown at the same site harbored communities of different complexity, a finding that is supported by the results of cultivation-dependent studies Raja et al, 2008).…”
Section: Introductionmentioning
confidence: 92%
“…The isolation of Methylobacterium spp. was not unexpected, since these previously described AAnPs (61,62) are known to occur in high numbers in the phyllosphere (1,2,4,(65)(66)(67)(68) and harbor genes for a photosynthetic reaction center as well as genes for bacteriochlorophyll biosynthesis based on completely genome-sequenced strains of this genus (with the exception of the nonpigmented nodulating root symbiont Methylobacterium nodulans) (69,70). However, the exclusive isolation of methylobacteria was not anticipated, because the diversity observed at the genomic level by metagenome studies suggested a higher diversity of pufM genes than was expected to be derived solely from Methylobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…For biofilm detachment from the algal surfaces, the cut algae were immersed in 2 ml of 0.1 M sodium pyrophosphate (Na 4 P 2 O 7 · 10H 2 O). Biofilm was dislodged by two rounds of sonication for 20 s at maximum intensity (Selecta, Barcelona, Spain), followed by 30 s on ice (23). Algal suspensions were centrifuged at 10,000 ϫ g for 2 min, and supernatants were discarded.…”
Section: Methodsmentioning
confidence: 99%